2023
DOI: 10.3390/agronomy13102612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Tillage Practices on Slope Erosion Characteristics of Peanut Field

Xinlan Liang,
Ke Song,
Youheng Zhang
et al.

Abstract: Under three rainfall intensities (60–90–120 mm/h) and four tillage practices (longitudinal ridge tillage, cross ridge tillage, flat tillage and hole sowing), field experiments was conducted during the podding stage of peanuts to investigate the changes in hydrodynamic parameters and the erosion response on purple soil slope cropland in order to reveal the soil and water conservation benefits of different tillage practices. The results showed that: (1) The sediment yield of the four tillage practices was ranked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Sustainable practices to control and mitigate soil erosion are essential worldwide, especially in environments that are more prone to erosion risks [1][2][3]. Many studies worldwide have shown that mulching is a key method for controlling runoff and soil erosion [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable practices to control and mitigate soil erosion are essential worldwide, especially in environments that are more prone to erosion risks [1][2][3]. Many studies worldwide have shown that mulching is a key method for controlling runoff and soil erosion [4,5].…”
Section: Introductionmentioning
confidence: 99%